Production machines maintenance based on digitalization - A. K. Tugengold; R. N. Voloshin; A. R. Yusupov; T. N. Kruglova (Advanced Engineering Research, 2019)
Introduction. Digital data and analytics transform the role of the production equipment maintenance. Analytical information of sensors placed on the product allows continuous monitoring of the production machines operation and their timely servicing. Thus, defects in technical equipment are identified, the analysis of which enables to develop algorithms for monitoring and forecasting, and to prevent equipment from overshooting the limits of the safe operation.Materials and Methods. Basic digitalization principles and the digital images structure are presented. A mathematical method is used to describe the digital image vector and the control system algorithm.Research Results. The achievements of the known systems of maintenance and digitalization of various machines are summarized. The application of a dynamic digital image made it possible to determine the desired levels of the production facilities maintenance. An optional version of monitoring the equipment state within the framework of the production digitalization concept is shown. It is based on the proposed algorithm for an autonomous control of the process state.Discussion and Conclusions. The construction of machine digital images in accordance with the main stages of its life cycle is described. The task of automated maintenance of machine tools based on digitalization is considered.